Chronic pancreatitis: aetiology, epidemiology and clinical presentation - Goh, Khean Lee (Malaysian Medical Association, 2005)
Chronic pancreatitis is a difficult disease to treat. Worldwide, alcohol is the most common aetiology but based on recent studies it is clear that genetic susceptibility plays an important role in determining disease. Several important genetic mutations have been identified. The prevalence of chronic pancreatitis appears to be lower in Asia although very high rates have been reported in parts of India. Severe intractable pain is the predominant presenting complaint of patients. The natural history of the disease and the onset of exocrine and endocrine insufficiency depend on the classification of disease as early onset, late-onset or alcohol associated. Complications of chronic pancreatitis are important and include pseudocyst formation, bile duct and duodenal strictures.